Factors Influencing Accessibility and Utilization of Library Resources by Nursing and Midwifery Students Abubakar Tafawa Balewa University Teaching Hospital (ATBUTH), Bauchi - Abubakar, Nasallah; B. Ajiji, Rifkatu; B. Ajiji, Rifkatu; Saleh Mohammed, Abdullahi; Maikudi, Ibrahim; Gital, Kasimu, Gidado (RA Journal of Applied Research, 2022)
The study was conducted on factors influencing accessibility and utilization of library resources by nursing and midwifery students Abubakar Tafawa Balewa University Teaching Hospital (ATBUTH), Bauchi. The study adopted a descriptive cross-sectional survey research design. Two objectives with two corresponding research questions and two null hypotheses were used. A total of 450 students comprising of 265 student nurses and 194 student midwives were used in this study. The entire population of the study was used to take care of subject attrition. Multistage sampling procedure with appropriate techniques was used. The instrument for data collection used in this study was a structured questionnaire. Three experts validated the instrument. From the duly completed copies of the questionnaire, the required data were generated and analyzed using mean and standard deviation statistics for answering the research questions and the one-way analysis of variance (ANOVA) for testing the hypothesis at 0.5. The findings revealed that there is accessibility of library resources among the students. The result further shows that students’ utilization of library resources. Out of the twelve (12) items in the Table, eight (8) of the items were accepted by student nurses as the mostly used library resources, while four (4) of the items were accepted by student midwives as the mostly used library resources. The three items accepted by both nursing and midwifery students as the mostly used library resources include “Reference books”, “Journals (hard copies)”, and “Submitted (past) students` project”. The study recommends that adequate computer with internet facilities and other electronic resources should be acquired and made more readily available for use by students. This is to complement the print resources which are already available in the library as well as enable the students to have access to online resources and data bases.